2023
DOI: 10.1371/journal.pone.0282244
|View full text |Cite
|
Sign up to set email alerts
|

Promoting GSDME expression through DNA demethylation to increase chemosensitivity of breast cancer MCF-7 / Taxol cells

Abstract: Objective Breast cancer is the most common and high-incidence cancer in women. It is mainly treated by surgery combined with chemoradiation. The main challenge in treating breast cancer patients is developing resistance to chemotherapeutics, so it is urgent to find potential strategies that can improve the chemotherapy effect of patients. In this study, we aimed to explore the role of GSDME methylation in the sensitivity of chemotherapy for breast cancer. Methods Here, we identified breast cancer MCF-7 / Tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Hypermethylation existed in the promoter of GSDME, and decitabine (DAC) could increase GSDME expression via reducing methylation by inhibiting DNA methyltransferase (DNMT) [ 9 , 30 ]. HCCLM3 and HepG2 were treated with DAC, and MTT assay showed that DAC wasn't cytotoxic to HCC cells (Supplementary Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Hypermethylation existed in the promoter of GSDME, and decitabine (DAC) could increase GSDME expression via reducing methylation by inhibiting DNA methyltransferase (DNMT) [ 9 , 30 ]. HCCLM3 and HepG2 were treated with DAC, and MTT assay showed that DAC wasn't cytotoxic to HCC cells (Supplementary Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin enhances complete response rates in patients with triple‐negative breast cancer patients by activating the lncRNA MEG3/NLRP3/caspase 1/GSDMD pyroptosis pathway 128 . Decitabine triggers GSDME expression by DNA demethylation, boosting pyroptosis and the chemosensitivity of MCF‐7/Taxol cells to Taxol 129 . TNFα‐induced apoptosis is converted to pyroptosis by antibiotic chemotherapy drugs (daunorubicin, DOX, epirubicin, and actinomycin D) that activate PD‐L1.…”
Section: Pyroptosis and Inflammasomes In Cancermentioning
confidence: 99%
“… 128 Decitabine triggers GSDME expression by DNA demethylation, boosting pyroptosis and the chemosensitivity of MCF‐7/Taxol cells to Taxol. 129 TNFα‐induced apoptosis is converted to pyroptosis by antibiotic chemotherapy drugs (daunorubicin, DOX, epirubicin, and actinomycin D) that activate PD‐L1. The interaction between p‐Stat3 and PD‐L1 during hypoxia facilitates its nuclear translocation, increasing GSDMC expression and triggering the GSDMC/caspase 8 pyroptosis pathway.…”
Section: Pyroptosis and Inflammasomes In Cancermentioning
confidence: 99%